Eksplorasi Metode Bermain Sebagai Strategi Efektif Pembelajaran Pendidikan Agama Islam pada Anak Usia Dini - Nilna Bariroh Hidayah; Siti Halimah; Nur Inayah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The purpose of this article is to explain how to teach Islamic religious education to young children through play tactics. Play describes a fun activity that can be done with or without tools. To strengthen the facts and information that underlie the discussion, this research uses a literature study approach, namely focusing on collecting, reviewing and evaluating various relevant literature sources. Various ways of using playing tactics and their significance in studying Islam will be discussed in this article. This is intended to help children understand religious concepts. According to research, children can learn Islamic teachings in a more interesting and enjoyable way if they use play techniques. Apart from that, play activities educate moral values, foster social relationships, and shape children's Islamic personalities.